Effects of state-dependent forward guidance, large-scale asset purchases and fiscal stimulus in a low-interest-rate environment - Günter Coenen; Carlos Montes-Galdón; Frank Smets (Goethe University Frankfurt, Center for Financial Studies (CFS), 2020)
We study the incidence and severity of lower-bound episodes and the efficacy of three types of state-dependent policies - forward guidance about the future path of interest rates, large-scale asset purchases and spending-based fiscal stimulus - in ameliorating the adverse consequences stemming from the effective lower bound on nominal interest rates. In particular, we focus on the euro area economy and examine, using the ECB's New Area-Wide Model, the consequences of the lower bound both for the near-term economic outlook, characterised by persistently low nominal interest rates and inflation, and in a lasting low-real-interest-rate world. Our findings suggest that, if unaddressed, the lower bound can have very substantial costs in terms of worsened macroeconomic performance. Forward guidance, if fully credible, is most powerful and can largely undo the distortionary effects due to the lower bound. A combination of imperfectly credible forward guidance, asset purchases and fiscal stimulus is almost equally effective, in particular when asset purchases enhance the credibility of the forward guidance policy via a signalling effect.
urn:nbn:de:hebis:30:3-527882
Keywords: E31; E32; E37; E52; E62; 330; effective lower bound; monetary policy; forward guidance; asset purchases; fiscal policy; euro area